Precipitable Water Vapour and Zenith Total Delay time series and models over Slovakia and vicinity - IGONDOVÁ, Miroslava; CIBULKA, Dušan (Contributions to Geophysics and Geodesy, 2010)
More than 50 permanent GNSS (Global Navigation Satellite Systems) stationsare processed continually within the Central European Permanent Network. ZenithTotal Delay (ZTD), one of the processing outputs, reflects a delay of the GNSS signalcaused by troposphere. Precipitable Water Vapour (PWV ) is calculated when groundmeteorological observations are available. Model of PWV over Slovakia and its vicinity isproduced using digital elevation model data for height correction. Real variation of PWVover the area shows a model of normalized PWV (nPWV ), which is created from PWVvalues reduced by theoretical PWV values corresponding to altitude and latitude of thestation. Time series of ZTD and PWV since 1996 and models of PWV and nPWV arepublished on the web page, using Web Map Service and other web technologies. Data arecontinually updated and can be downloaded for free.